Analisis Penggunaan Model Discovery Learning Dan Pengaruhnya Terhadap Keterampilan Proses Sains Pada Pembelajaran IPA Di SMPN 41 Muaro Jambi - Listiani Listiani (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2022)
In the 2013 curriculum, students are required to be active in learning. One of the learning models that are suitable to meet current needs is the discovery learning model. Based on the learning model, learning is directed at the active involvement of students through process activities. Process activities are obtained from experience through experimental activities, to get process activities required a skill called process skills. Skills in carrying out activities related to science are commonly called science process skills (KPS) which are a complex set of abilities that are commonly used in conducting scientific investigations in the learning process. This study aims to determine the use of discovery learning learning models and the effect of discovery learning models on science process skills in science learning for class VII SMPN 41 Muaro Jambi. This research was conducted on science learning, especially the material of heat and its transfer with the number of students 30 people. This research method uses the type of research concurrent embedded mixed methods. The results of the study using the discovery learning learning model in science learning in class VII SMPN 41 Muaro Jambi quite received a good response from the students, it can be seen from the pre-test and post-test test scores that obtained a much better score indicated by the average value. The pre-test average was 44.4 and the post-test mean was 78.133. Discovery learning learning model in science learning has a significant influence. The results of the calculation of hypothesis testing with paired t-test or t-Test: Paired Two Sample For Means show tcount = -15,445 and ttable = -2,045. In conclusion, because tcount > ttable then Ho is rejected and Ha is accepted.